2021
DOI: 10.3390/mti5080040
|View full text |Cite
|
Sign up to set email alerts
|

User Monitoring in Autonomous Driving System Using Gamified Task: A Case for VR/AR In-Car Gaming

Abstract: Background: As Automated Driving Systems (ADS) technology gets assimilated into the market, the driver’s obligation will be changed to a supervisory role. A key point to consider is the driver’s engagement in the secondary task to maintain the driver/user in the control loop. This paper aims to monitor driver engagement with a game and identify any impacts the task has on hazard recognition. Methods: We designed a driving simulation using Unity3D and incorporated three tasks: No-task, AR-Video, and AR-Game tas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…From this, we concluded that the inclusion of additional tasks did not negatively affect hazard recognition. This is in agreement with the same findings we identified in a related study reported in (Muguro et al, 2021). Research on take-over time, which hazard recognition points to, has indicated that cognitive-and visual-loaded secondary tasks do not have major impacts on take-over performance (Happee et al, 2017;Zeeb et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From this, we concluded that the inclusion of additional tasks did not negatively affect hazard recognition. This is in agreement with the same findings we identified in a related study reported in (Muguro et al, 2021). Research on take-over time, which hazard recognition points to, has indicated that cognitive-and visual-loaded secondary tasks do not have major impacts on take-over performance (Happee et al, 2017;Zeeb et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…This way, vigilance can be supported for extended periods. More details on this have been discussed in (Muguro et al, 2021). In this regard, the results support the idea that ADS-human handover would be enhanced through the identified driver engagement levels, where the system only performs handover when the user is demonstrably vigilant.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation